2013
DOI: 10.9790/1684-0746774
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of the Effect of Fuel Injector nozzle holes on Direct Injection Diesel Engine

Abstract: Fuel injection parameters play an important role in diesel engine performance for obtaining proper combustion. The performance and emission characteristics of diesel engine depend on many parameters. The important parameters which influence the performance and emission of diesel engine are fuel injection pressure, fuel nozzle holes and its size. An experimental study was performed on a light duty direct injection diesel engine at 200 bar, 220 bar and 240 bar injection pressure to study its effect on performanc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
18
0

Year Published

2016
2016
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 5 publications
0
18
0
Order By: Relevance
“…The combustion duration is lower at due to the small fuel spray droplets and complete combustion of the fuel in the combustion chamber. Too high injection pressure may be responsible to higher velocity of droplet which will leave away without mixing air properly with fuel[21].It can be observed that the values of CBWD10 at 200, 210 220, 230 and 240 bar are found to be about 37.4, 36.9, 35.1, 34.8 and 34.4 °CA respectively, at the maximum brake power.…”
mentioning
confidence: 84%
“…The combustion duration is lower at due to the small fuel spray droplets and complete combustion of the fuel in the combustion chamber. Too high injection pressure may be responsible to higher velocity of droplet which will leave away without mixing air properly with fuel[21].It can be observed that the values of CBWD10 at 200, 210 220, 230 and 240 bar are found to be about 37.4, 36.9, 35.1, 34.8 and 34.4 °CA respectively, at the maximum brake power.…”
mentioning
confidence: 84%
“…The impact of engine settings on a DI engine's performance and emission characteristics has been examined in several studies related to diesel and gasoline. Kumbhar et al [4] used computation fluid dynamics CFD codes with a combustion model to test four different nozzle throat diameters and their influence upon the engine performance, emissions, as well as spraying features. They discovered that improvements in spray cone angle, fuel atomization, and effective air-fuel mixture resulted to a 0.230 mm nozzle throat diameter, which led to the highest in-cylinder temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%
“…The first law of thermodynamics, equation of energy, mass conserving, equation of state, and mass fraction burned were all used in the creation of the software program. The study was carried out at five different nozzle diameters (0.250, 0.350, 0.450, 0.550, and 0.650 mm) and nozzle hole numbers (4,6,8,10,12). The results show that the GDI engine's performance and emissions are significantly influenced by variations in nozzle hole diameter and number.…”
mentioning
confidence: 99%
“…It has been used for further research and scientific papers in the field of diesel engine processes [7]. Similar procedures of experimental determination of injection parameters, due to their crucial influence on working processes in engine cylinders, were also applied by other researchers [8][9][10][11][12][13][14][15][16]. Comparative experimental results of in-cylinder pressure flow and injection parameters in direct injection diesel engines are shown in [8], where standard diesel fuel and emulsion of water and diesel fuel are used.…”
Section: Introductionmentioning
confidence: 99%